A low‐profile circularly polarized dielectric patch antenna and array. Issue 3 (28th November 2019) - Yang, Ling‐Ling; Li, Yun‐Li; Yang, Wen‐Wen; Yang, Yong‐Jie; Chen, Jian‐Xin
Abstract: A square dielectric patch (DP) resonator fusing with the bottom substrate is studied for designing low‐profile circularly polarized (CP) antenna. Based on the theoretical investigation using the constructed analysis model, it can be found that the proposed DP resonator possesses a pair of degenerate dominate modes (TM101 and TM011 ), which can be split by introducing perturbations on the DP resonator and then used to design CP antenna fed by a microstrip line directly. To verify the proposed idea, a 2 × 2 array fed by a dual Marchand balun network is designed and implemented. Reasonable agreement between the measured and simulated results is observed. Experimental results show that a measured impedance bandwidth is 380 MHz (5.18‐5.56 GHz) for |S11 | < −10 dB and the 3‐dB axial ratio bandwidth is 90 MHz (5.32‐5.41 GHz). The measured gain is up to 11.77 dBic with a cross polarization of about −20 dB in the boresight direction.